2019
DOI: 10.1038/s41598-019-55297-2
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of N-acetyl cysteine prevents osteoarthritis development and progression in a rat model

Abstract: The number of osteoarthritis patients is increasing with the rise in the number of elderly people in developed countries. Osteoarthritis, which causes joint pain and deformity leading to loss of activities of daily living, is often treated surgically. Here we show that mechanical stress promotes accumulation of reactive oxygen species (ROS) in chondrocytes in vivo, resulting in chondrocyte apoptosis and leading to osteoarthritis development in a rat model. We demonstrate that mechanical stress induces ROS accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 51 publications
(48 reference statements)
1
17
0
Order By: Relevance
“…Taken together, our results confirm the therapeutic potential of inhibiting ROS to treat OA. Indeed, it has already been demonstrated that oral administration of the anti-oxidant N-acetyl cysteine (NAC) protects against OA in the rat [ 32 ] and reduces hypertrophy in the growth plate of mice [ 28 ]. Future studies could use NAC to evaluate its impact on oxPTM-CII generation, hypertrophy, and OA initiation and progression in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our results confirm the therapeutic potential of inhibiting ROS to treat OA. Indeed, it has already been demonstrated that oral administration of the anti-oxidant N-acetyl cysteine (NAC) protects against OA in the rat [ 32 ] and reduces hypertrophy in the growth plate of mice [ 28 ]. Future studies could use NAC to evaluate its impact on oxPTM-CII generation, hypertrophy, and OA initiation and progression in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…This study together with results from others con rms the therapeutic potential of inhibiting ROS to treat OA. Indeed, it was demonstrated that oral administration of the anti-oxydant N-acetyl cysteine (NAC) protect against OA in the rat (32) and reduces hypertrophy in the growth plate of mice (28). Future studies could use NAC to evaluate its impact on oxPTM-CII generation, hypertrophy and OA initiation and progression in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…NAC was capable of protecting the mature microtissues from the deteriorating effect of the monomer. This ability of NAC to defend tissues and their components from destruction is relatable to its roles in preventing oxidative degradation of biological membranes and/or degradation of MMPs [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%